1994
DOI: 10.1287/moor.19.4.780
|View full text |Cite
|
Sign up to set email alerts
|

Lemke Paths on Simple Polytopes

Abstract: Lemke paths are often used in the solution of nonlinear programming problems. We investigate a number of properties of Lemke paths, motivated by the d-step conjecture for linear programming. Some negative results are presented, including families of Lemke paths, for which the length of the shortest grows exponentially, joining pairs of vertices of a sequence of polytopes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…This is always so in our special case (3) where q = 1, C = −M, and P is bounded. For a simple polytope P in (3), a "Lemke path" (see also Morris, 1994) is obtained for a given missing label w in [m] as follows. Start at a CL vertex, for example 0, and "pivot" along the unique edge that leaves the facet with label w. This reaches a vertex v on a new facet F with label k. If k = w, then v is CL and the path terminates.…”
Section: Labeled Polytopes and Signed Matchingsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is always so in our special case (3) where q = 1, C = −M, and P is bounded. For a simple polytope P in (3), a "Lemke path" (see also Morris, 1994) is obtained for a given missing label w in [m] as follows. Start at a CL vertex, for example 0, and "pivot" along the unique edge that leaves the facet with label w. This reaches a vertex v on a new facet F with label k. If k = w, then v is CL and the path terminates.…”
Section: Labeled Polytopes and Signed Matchingsmentioning
confidence: 99%
“…The main result of this section (Theorem 12) states that in an Euler digraph, a second perfect matching of opposite sign can be found in polynomial (in fact, near-linear) time. This holds in contrast to the complementary pivoting algorithm, which can take exponential time; Casetti, Merschen, and von Stengel (2010) have shown how to apply results of Morris (1994) for this purpose. However, the pivoting algorithm takes linear time in a bipartite Euler graph, and a variant can be used to find an oppositely signed matching in a bipartite graph that has no source or sink (Proposition 13).…”
Section: Signed Perfect Matchingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morris [47] have found a infinite family of polytopes for which the number of pivots performed by the Lemke algorithm is exponential. More recently, a family of bimatrix games instances leading also to an exponential number of pivots has been found by Savani and von Stengel [55].…”
Section: 2mentioning
confidence: 99%
“…Savani and von Stengel [8] (see also [6]) have shown that the Lemke-Howson algorithm is exponential relative to the size of the matrices defining the game, not necessarily exponential relative to the number of simplices defined by the matrices. Proof.…”
Section: Nash Equilibria For 2-person Gamesmentioning
confidence: 99%